Age is not a bar to PCI: Insights from the long‐term outcomes from off‐site PCI in a real‐world setting. (2nd July 2017) - Gerber, Robert T.; Arri, Satpal S.; Mohamed, Mohamed O.; Dhillon, Gurpreet; Bandali, Alykhan; Harding, Idris; Gifford, Jeremy; Sandler, Belinda; Corbo, Ben; McWilliams, Eric
Abstract : Objectives: We sought to analyze the percutaneous coronary intervention (PCI) outcomes of very elderly patients (V. Eld. group, age >80 years) and compare their outcomes to a less elderly cohort (Eld. group, age 75‐80 years) traditionally reported in the literature. Background: Limited data exist on peri‐procedural and long‐term outcomes following PCI in the V. Eld. (age >80 years), with under‐representation of this cohort in randomized controlled trials. These patients present with advanced complex coronary disease and multiple comorbidities. Methods: All 580 consecutive patients aged ≥75 years (age 80 ± 4.9 years, 57.4% males) undergoing PCI between April 2006 and November 2011 were included. A total of 624 consecutive lesions were identified and analyzed. All V. Eld. patients ( n  = 253) were subsequently selected, and their outcomes compared to Eld. patients ( n  = 327). Mean follow‐up was 30.8 ± 2.7 months with 98% clinical follow‐up achieved. Results: All comparative data are expressed as (V. Eld. vs Eld.) unless otherwise specified. All‐cause mortality was significantly higher in the V. Eld. group (11.9% vs 6.1%), although this did not translate into a significant difference in cardiac mortality (6.3% vs 3.7%) or major adverse cardiac and cerebrovascular events (16.2% vs 12.5%). The composite incidence of myocardial infarction (MI), stroke, definite/probable stent thrombosis, and TIMI major bleed was 4.7%, 1.4% 1.9%, and 6.4%, respectively with no significant difference between both cohorts. Conclusions: This study demonstrates an acceptable occurrence of MI, death, repeat intervention, and stent thrombosis in a high‐risk group of V. Eld. patients with de novo lesions. Age alone in the absence of other non‐cardiac factors should not prohibit a patient from access to PCI.